Risk Factors for Hypertension in Guraping Village, Tidore - Maya Sari Soamole; Norma B. Toduho; Hestyn Amelia; Safira Pasimanyeku (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Hypertension or also mentioned as The Silent Killer is increased of blood pressure ≥140/90mmHg, it cause serious disease or even death. This study used descriptive analysis with a cross-sectional study design. There are 251 respondents as become sampled of research that using to the Slovin formula (alpha 0.05). It based of the descriptive analysis results for hypertension risk factor variables, it concluded that the frequency of The smoking people in the house was 170 (67.7%), 77 (30.7%) respondents consumed The salty foods between 3-4 times per week, 94 (37.5%) respondents consumed The fatty foods between 3-4 times per week, 105 (41.8%) respondents consumed The seasonings powder more than once per day, 68 (27.1%) respondents consumed the instant noodles between 3-4 times per week, and 112 (44.6%) respondents lack to physical activity. It concluded that the risk factors for hypertension in the community are still high. It is hoped that there will be collaboration with health workers to reduce the risk factors for hypertension by providing regular education, Integrated community development post (posbindu) activities in the Guraping sub-district community as a promotive and preventive program to avoid hypertension and provide curative and rehabilitative services as a treatment program.